Contribution of the Mapalus House Building Tradition: Strengthening Civic Culture and Bhinneka Tunggal Ika in Tombatu Dua Tengah Village, North Sulawesi - Thezalonica Jecika Mania; Nasiwan Nasiwan (Journal of Social Research, 2025)
Citizen culture and Bhinneka Tunggal Ika are a set of ideas or concepts that contain positive values and become the identity of a nation. However, with globalization, people's lifestyles have shifted to modern lifestyles, because it is one of the crucial problems that makes people no longer preserve citizen culture and the values contained in the motto Bhinneka Tunggal Ika as a national identity. This study aims to analyze the contribution of the Mapalus tradition of house building to strengthen citizen culture and Bhinneka Tunggal Ika in Tobatu Dua Tengah village. This study is an ethnographic study with a qualitative approach. The research data collection technique uses in-depth interview techniques, observation, and documentation. The results of the study indicate that the implementation of the Mapalus tradition of house building can strengthen citizen culture in terms of language, knowledge, kinship and social organization, and art. These findings are in line with Hall's theory, that cultural identity comes from ancestral heritage, has certain elements and values that strengthen the cultural identity of a region. Mapalus house construction also provides reinforcement of bhinneka tunggal ika in the aspect of strengthening social solidarity, resource sharing, collective problem solving, uniting various social groups, non-formalistic principles, convergent, pluralistic and multicultural, and the spirit of mutual cooperation. This finding is in line with Robert's theory that high social connectedness, achieved through joint activities, can increase trust and cooperation between community members.